Comparing geographical distribution of community‐based physiotherapists and family physicians across Saskatchewan. (27th October 2015) - Shah, Tayyab I.; Bath, Brenna; Milosavljevic, Stephan
Key Messages: This comparative analysis between the spatial accessibility to physiotherapists (PTs) and family physicians (FPs) highlights poorly served municipalities through mapping. A large volume of population age 65 and over, low‐income individuals, recent immigrants, and those of aboriginal status/ethnicity have reduced access to PT services particularly in rural and remote municipalities. Abstract : This study set out to investigate differences in geographic accessibility to community‐based physiotherapists (PTs) and family physicians (FPs), identify poorly served communities across Saskatchewan, and explore the association of health service provider distribution with population health characteristics. A cross‐sectional GIS‐based approach examined spatial distributions of PTs and FPs across Saskatchewan using a three‐step floating catchment area (3SFCA) method. Data regarding PTs (n = 558) and FPs (n = 982) were gathered from provincial regulatory bodies. An access score was calculated using a 25km buffer zone. Crosstab analysis was applied to investigate the distribution of FP and PT services in association with key socio‐demographic variables. We found substantial variations in spatial distribution of PT and FP services across Saskatchewan. A considerable proportion of the population with potentially high health care needs is associated with poor accessibility to both PT and FP services, with a greater proportion of the population facing limited access to PT services. This comparative analysis between the spatial distributions of PTs and FPs demonstrates reduced services in a number of rural and urban Saskatchewan communities. This information contributes to a better understanding of accessibility to PT and FP services which may inform health workforce planning policies and strategies at provincial and local levels.